Occurrence and distribution of antifouling biocide Irgarol-1051 in coral reef ecosystems, Zanzibar. Issue 1 (15th August 2016) - Sheikh, Mohammed A.; Juma, Fatma S.; Staehr, Peter; Dahl, Karsten; Rashid, Rashid J.; Mohammed, Mohammed S.; Ussi, Ali M.; Ali, Hassan R.
Abstract: 2-methythiol-4- tert -butylamino-6-cyclopropylamino- s -triazine (Irgarol-1051) has been widely used as effective alternative antifouling paint in marine structures including ships. However, it has been causing deleterious effects to marine organisms including reef building corals. The main objective of this study was to establish baseline levels of Irgarol-1051 around coral reefs and nearby ecosystems along coastline of Zanzibar Island. The levels of Irgarol-1051 ranged from 1.35 ng/L around coral reefs to 15.44 ng/L around harbor with average concentration of 4.11 (mean) ± 0.57 (SD) ng/L. This is below Environmental Risk Limit of 24 ng/L as proposed by Dutch Authorities which suggests that the contamination is not alarming especially for coral reef ecosystem health. The main possible sources of the contamination are from shipping activities. This paper provides important baseline information of Irgarol-1051 around the coral reef ecosystems within the Western Indian Ocean (WIO) region and may be useful for formulation of marine conservation strategies and policies. Highlights: Irgarol 1051 are emerging pollutants in the coral reef ecosystem. This paper provides a baseline information of antifouling biocide in coral reefs. The detected levels do not pose any serious threat to the marine organisms.